Multıparametric Prostate Magnetic Resonance Imaging Before Radical Prostatectomy: Can it Predict Histopathology? - Sahin, Mehmet; Kizilay, Fuat; Guler, Ezgi; Sarsik, Banu; Harman, Mustafa; Kalemci, Serdar; Simsir, Adnan; Cureklibatir, Ibrahim (Urology Journal, 2020)
Purpose: We aimed to investigate the histopathological correlation of the suspected prostate malignancy detected in multiparametric prostate magnetic resonance imaging (mpMRI). Materials and Methods: The data of 93 patients underwent radical prostatectomy and had preoperative mpMRI were examined. Age and pre-operative Prostate-Specific Antigen value were retrospectively collected from patient files. The pathology specimens were examined again and post-operative ISUP grade group, other pathological findings (seminal vesicle invasion, lymph node involvement and extraprostatic extension), pre-operative mpMRI were re-examined and PIRADS score, extracapsular extension, seminal vesicle invasion, neurovascular bundle invasion, lymph node involvement and ADC values were recorded. Results: 151 (92,07%) of 164 lesions detected in mpMRI were histopathologically correlated. 80% of patients with seminal vesicle invasion (P < 0.001), 28.8% of patients with extracapsular extension (P < 0.052) and 42.9% of patients with lymph node involvement (P = .001) in mpMRI were histopathologically correlated. A significant relationship was found between PIRADS scores and ISUP grade groups (P < 0.001). There was a negative correlation between ADC values and ISUP grade groups (P < 0.001). Conclusion: Our study showed that the lesions detected by mpMRI showed a high histopathological correlation.